KnowledgeBoat Logo

Mathematics

From the figure (2) given below, find the value of :

(i) sin x

(ii) cot x

(iii) cot2 x - cosec2 x

(iv) sec y

(v) tan2 y - 1cos2y\dfrac{1}{\text{cos}^2 y}

From the figure, find the value of (i) sin x (ii) cot x (iii) cot^2 x - cosec^2 x (iv) sec y. Trigonometrical Ratios, ML Aggarwal Understanding Mathematics Solutions ICSE Class 9.

Trigonometrical Ratios

47 Likes

Answer

In right angled ∆ABD,

From the figure, find the value of (i) sin x (ii) cot x (iii) cot^2 x - cosec^2 x (iv) sec y. Trigonometrical Ratios, ML Aggarwal Understanding Mathematics Solutions ICSE Class 9.

By pythagoras theorem we get,

⇒ AD2 = AB2 + BD2

⇒ AD2 = 32 + 42

⇒ AD2 = 9 + 16

⇒ AD2 = 25

⇒ AD = 25\sqrt{25}

⇒ AD = 5

In right angled triangle DBC,

By pythagoras theorem we get,

⇒ DC2 = DB2 + BC2

⇒ 122 = 42 + BC2

⇒ BC2 = 122 - 42

⇒ BC2 = 144 - 16

⇒ BC2 = 128

⇒ BC = 128\sqrt{128}

⇒ BC = 828\sqrt{2}.

(i) sin x = PerpendicularHypotenuse\dfrac{\text{Perpendicular}}{\text{Hypotenuse}}

= BDAD=45\dfrac{BD}{AD} = \dfrac{4}{5}.

Hence, sin x = 45\dfrac{4}{5}.

(ii) cot x = BasePerpendicular\dfrac{\text{Base}}{\text{Perpendicular}}

= ABBD=34\dfrac{AB}{BD} = \dfrac{3}{4}.

Hence, cot x = 34\dfrac{3}{4}.

(iii) cosec x = HypotenusePerpendicular\dfrac{\text{Hypotenuse}}{\text{Perpendicular}}

= ADBD=54\dfrac{AD}{BD} = \dfrac{5}{4}.

Substituting values in cot2 x - cosec2 x we get :

=(34)2(54)2=9162516=1616=1.= \Big(\dfrac{3}{4}\Big)^2 - \Big(\dfrac{5}{4}\Big)^2 \\[1em] = \dfrac{9}{16} - \dfrac{25}{16} \\[1em] = -\dfrac{16}{16} \\[1em] = -1.

Hence, cot2 x - cosec2 x = -1.

(iv) sec y = HypotenuseBase\dfrac{\text{Hypotenuse}}{\text{Base}}

= CDBC=1282=322\dfrac{CD}{BC} = \dfrac{12}{8\sqrt{2}} = \dfrac{3}{2\sqrt{2}}.

Hence, sec y = 322\dfrac{3}{2\sqrt{2}}.

(v) tan y = PerpendicularBase\dfrac{\text{Perpendicular}}{\text{Base}}

= BDBC=482=122\dfrac{BD}{BC} = \dfrac{4}{8\sqrt{2}} = \dfrac{1}{2\sqrt{2}}.

Given,

tan2y1cos2y(122)2sec2y18(322)21898198881.\Rightarrow \text{tan}^2 y - \dfrac{1}{\text{cos}^2 y} \\[1em] \Rightarrow \Big(\dfrac{1}{2\sqrt{2}}\Big)^2 - \text{sec}^2 y \\[1em] \Rightarrow \dfrac{1}{8} - \Big(\dfrac{3}{2\sqrt{2}}\Big)^2 \\[1em] \Rightarrow \dfrac{1}{8} - \dfrac{9}{8} \\[1em] \Rightarrow \dfrac{1 - 9}{8} \\[1em] \Rightarrow \dfrac{-8}{8} \\[1em] \Rightarrow -1.

Hence, tan2y1cos2y=1\text{tan}^2 y - \dfrac{1}{\text{cos}^2 y} = -1

Answered By

28 Likes


Related Questions